Women art critics in nineteenth-century France : vanishing acts (University of Delaware Press, 2013)
This book is the first sustained study of a corpus of writings by women art critics active in nineteenth-century France that have all but "vanished" from the historical record. Written by scholars in art history and in literature, the essays employ a variety of interdisciplinary approaches and methodologies to study the women's reception of specific artworks and aesthetic movements in the nineteenth century, the intersections of aesthetics and politics in their essays, and their rhetorical strategies and literary styles